2020
DOI: 10.2174/2215083805666190612143120
|View full text |Cite
|
Sign up to set email alerts
|

In the Back Drop of Overuse of Synthetic Drugs, can Botanicals be One of the Answers: A Pilot Study on the Medicinal Use of Chlorophytum and Curcuma by Tribals of Central India

Abstract: Background: In several recent surveys, it has been found that more people suffer because of over and indiscriminate use of synthetic drugs, chemicals and antibiotics, particularly with regard to issues like drug sensitivity, resistance, immune disturbances, and economic burdens, ultimately leading to a weak prognosis of a large number of diseases, eventually defeating the purpose of medicinal efficacy. We propose the old age use of scientifically validated natural compounds of plants and their products for a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…C. borivilianum has been used for over 4,000 years, according to the Hindu epic Srimad Bhagawat. It belongs to the “Vajikarana Rasayana” group of Ayurvedic plants, which are utilized for rejuvenation ( Miraj et al, 2020 ; Verma et al, 2020 ) and revitalization characteristics in order to improve sexual dynamics ( Puri, 2003 ) and alleviate sexual dysfunction. This is also the basis for Kamasutra’s medical recommendations ( Hooper, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…C. borivilianum has been used for over 4,000 years, according to the Hindu epic Srimad Bhagawat. It belongs to the “Vajikarana Rasayana” group of Ayurvedic plants, which are utilized for rejuvenation ( Miraj et al, 2020 ; Verma et al, 2020 ) and revitalization characteristics in order to improve sexual dynamics ( Puri, 2003 ) and alleviate sexual dysfunction. This is also the basis for Kamasutra’s medical recommendations ( Hooper, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in Ayurveda, C. borivilianum L. is considered an important medicine in the Vajikarana (sexual enhancement and improved progeny) segment (Agnivesha and Dridhabala, 2006). Several studies reported that C. borivilianum plays an important role in rejuvenation (Miraj et al, 2020;Verma et al, 2020) and revitalization characteristics to improve sexual dynamics (Puri, 2003) and alleviates sexual dysfunction. Furthermore, various parts of C. borivilianum are prescribed by Ayurveda practitioners for improving health issues including diabetes, infections, and cirrhosis, among others (Singh et al, 2011).…”
Section: Introductionmentioning
confidence: 99%